Transcriptome profiling reveals regulatory mechanisms underlying corolla senescence in petunia. Issue 1 (1st April 2018) - Wang, Hong; Chang, XiaoXiao; Lin, Jing; Chang, Youhong; Chen, Jen-Chih; Reid, Michael S; Jiang, Cai-Zhong
Abstract: The genetic regulatory mechanisms that govern natural corolla senescence in petunia are not well understood. To identify key genes and pathways that regulate the process, we performed a transcriptome analysis in petunia corolla at four developmental stages, including corolla fully opening without anther dehiscence (D0), corolla expansion, 2 days after anthesis (D2), corolla with initial signs of senescence (D4), and wilting corolla (D7). We identified large numbers of differentially expressed genes (DEGs), ranging from 4626 between the transition from D0 and D2, 1116 between D2 and D4, a transition to the onset of flower senescence, and 327 between D4 and D7, a developmental stage representing flower senescence. KEGG analysis showed that the auxin- and ethylene-related hormone biosynthesis and signaling transduction pathways were significantly activated during the flower development and highly upregulated at onset of flower senescence. Ethylene emission was detected at the D2 to D4 transition, followed by a large eruption at the D4 to D7 transition. Furthermore, large numbers of transcription factors (TFs) were activated over the course of senescence. Functional analysis by virus-induced gene silencing (VIGS) experiments demonstrated that inhibition of the expression of TFs, such as ethylene-related ERF, auxin-related ARF, bHLH, HB, and MADS-box, significantly extended or shortened flower longevity. Our data suggest that hormonal interaction between auxin and ethylene may play critical regulatory roles in the onset of natural corolla senescence in petunia. Flower development: When to wilt: How long flowers bloom is determined by genes that alter levels of the plant hormones ethylene and auxin. When flowers are no longer needed, plants signal them to die; the underlying genetic mechanisms are not well understood. Cai-Zhong Jiang at the University of California, Davis and co-workers used genetic analysis to determine how the signals for petal death are encoded. They studied petunia flowers at four stages: opening, pollen release, onset of wilting, and fully wilted, and identified over 5000 genes that were turned up or down. The master switches for petal death were found to be genes controlling ethylene and auxin levels. Using a virus to artificially switch off several genes, the researchers identified genes that shorten or extend flower life by up to three days. These results may be useful in plant breeding.